Micromechanics of elastic lamellae: unravelling the role of structural inhomogeneity in multi-scale arterial mechanics. Issue 147 (17th October 2018) - Yu, Xunjie; Turcotte, Raphaël; Seta, Francesca; Zhang, Yanhang
Abstract : Microstructural deformation of elastic lamellae plays important roles in maintaining arterial tissue homeostasis and regulating vascular smooth muscle cell fate. Our study unravels the underlying microstructural origin that enables elastic lamellar layers to evenly distribute the stresses through the arterial wall caused by intraluminal distending pressure, a fundamental requirement for tissue and cellular function. A new experimental approach was developed to quantify the spatial organization and unfolding of elastic lamellar layers under pressurization in mouse carotid arteries by coupling physiological extension–inflation and multiphoton imaging. Tissue-level circumferential stretch was obtained from analysis of the deformation of a thick-walled cylinder. Our results show that the unfolding and extension of lamellar layers contribute simultaneously to tissue-level deformation. The inner lamellar layers are wavier and unfold more than the outer layers. This waviness gradient compensates the larger tissue circumferential stretch experienced at the inner surface, thus equalizing lamellar layer extension through the arterial wall. Discoveries from this study reveal the importance of structural inhomogeneity in maintaining tissue homeostasis through the arterial wall, and may have profound implications on vascular remodelling in aging and diseases, as well as in tissue engineering of functional blood vessels.